A comprehensive review of the physico-mechanical properties of masonry units incorporating municipal solid waste - Nikmah, Norma Wihdatun; Abdullah, Maaz; Khan, Sadique; Mohamed, Mohamed Abdulqadir; Al-Fakih, Amin (Frontiers in Built Environment, 2025)
The growing demand for sustainable construction materials and the urgent need for effective municipal solid waste (MSW) management have led to the exploration of MSW incorporation into masonry unit production. This review critically evaluates various MSW-derived materials, including paper sludge, food waste, plastics, rubber, leather, and glass waste, in fabricating bricks and blocks. The study compares data from numerous case studies, examining how MSW integration affects physico-mechanical properties such as bulk density, compressive, tensile, flexural strength, thermal conductivity, water absorption, and porosity. The findings indicate that while including MSW often reduces density and improves thermal insulation, it can negatively impact mechanical strength beyond certain thresholds. Thermal conductivity values in MSW-based bricks were decreased significantly across a wide range of waste types, achieving values as low as 0.17 W/mK, demonstrating enhanced insulating capabilities that support energy-efficient building design. However, with optimized mix proportions and processing techniques, many MSW-based masonry units meet or exceed performance standards for specific structural and non-structural applications. This review underscores the need for further research into waste compatibility, long-term performance, and standardization to enable large-scale adoption of MSW-based construction materials.